Clinical validation of the AMTAS automated audiometer. (May 2013) - Eikelboom, Robert H.; Swanepoel, De Wet; Motakef, Shahpar; Upson, Gemma S.
Abstract Objective: To validate the air- and bone-conduction AMTAS automated audiometry system. Design: Prospective study. Test-retest reliability was determined by assessing adults with AMTAS air- and bone-conduction audiometry. Accuracy was determined by comparing AMTAS and manual audiometry conducted on adults. AMTAS testing was conducted in a quiet room and manual audiometry in a sound booth. Study sample: Ten participants for test-retest reliability tests and 44 participants to determine accuracy were included. Participants had varying degrees of hearing loss. Results: For test-retest reliability the overall difference in air-conduction hearing thresholds (n = 119) was 0.5 dB. The spread of differences (standard deviation of absolute differences) was 4.9 dB. For bone-conduction thresholds (n = 99) the overall difference was − 0.2 dB, and the spread of differences 4.5 dB. For accuracy the overall difference in air-conduction hearing thresholds (n = 509) between the two techniques was 0.1 dB. The spread of differences was 6.4 dB. For bone-conduction thresholds (n = 295) the overall difference was 0 dB, and the spread of differences 7.7 dB. Conclusions: Variations between air- and bone-conduction audiometry for automated and manual audiometry were within normally accepted limits for audiometry. However, AMTAS thresholds were elevated but not significantly different compared to other contemporary studies that included an automated audiometer.